Oficina na atenção psicossocial: experimentações com a palavra - Hernandes, Kátia Murray; Bruniera, Marcelo de Souza; Luzio, Cristina Amélia [UNESP] (My University, 2011)
The Word Workshop was created in 2004, as an activity of the training period in Psychosocial Care in the Collective Health, a discipline that is part of the curriculum of the Psychology course offered by the State of São Paulo’s University “Júlio de Mesquita Filho”/UNESP, campus of Assis. Initially, it is possible to affirm that the Word Workshop contributes to stimulate the flow of the words through the discussion of tales, short stories, poetry, jokes and news. The Word Workshop is considered an effort towards the guarantee of a space where the users of the mental health care service can share varied experiences and it is also thought as an attempt that can, potentially, bring up the conditions through which some existential meanings may possibly be forked. Such a space-instrument allows the mental health care users to speak about life and their interests rather than to keep focused in symptoms and complains. These ones, by their turn, are expressed through metaphors, unprecedented speech experiences and new sensitivity regimes. The critical analysis of the singular experience of the Word Workshop, that understands the words as agents of social transformation, was conceived with the support of Enrique Pichon-Rivière’s and Paulo Freire’s theories. From this first theoretical reading, it is possible to make an incursion through the scenery of the Psychosocial Care Workshops, paying special attention to their potential and to the risks related to crystallized practices.

A Oficina da Palavra foi criada em 2004, como atividade do estágio curricular em “Atenção Psicossocial na Saúde Coletiva” do curso de Psicologia da UNESP/Assis com o objetivo geral de estimular a circulação da palavra, através da discussão de contos, histórias, “causos”, piadas, poesias e produções jornalísticas. De início, considera-se que Oficina da Palavra pode contribuir substancialmente ao garantir um espaço para a manifestação e socialização dos mais diversos saberes e, em potência, criar condições para que determinados sentidos existenciais se bifurquem. Tal espaço-dispositivo possibilita ao usuário da saúde mental falar da vida e dos interesses, para além de queixas e sintomas, metaforizando-os, através de experimentações inéditas da linguagem e de novos regimes de sensibilidade. Aportando-se teoricamente em Enrique Pichon-Rivière e Paulo Freire, elaborou-se uma análise crítica desta experiência singular que, na tentativa de promover bons encontros, concebe a palavra como agente de conscientização e transformação social. A partir desta primeira leitura teórica-crítica, vislumbra-se uma possível incursão no cenário das oficinas na Atenção Psicossocial de cuidado, atentando-se para as potencialidades e perigos desta prática já instituída.
Keywords: Psychology; Psychiatric Reform; Workshops; Mental health; Psicologia; Reforma Psiquiátrica; Oficina; Saúde Mental